The Incidence and Characteristics of Misdiagnosed Covid-19 Patients with Dengue Fever Infections at Udayana University Hospital in 2020-2021 - Adiputra, I Komang Hotra; Swastika, I Kadek; Diarthini, Ni Luh Putu Eka; Sudarmaja, I Made; Purnamasidhi, Cokorda Agung Wahyu (Institute of Topical Disease Universitas Airlangga, 2023)
The rise in dengue fever in recent decades combined with the emergence of COVID-19 at the end of 2019, has created new challenges in the healthcare sector. This research is a descriptive study with a cross-sectional research design and using medical record data at Udayana University Hospital in 2020–2021. According to the study, 1.22% cases of misdiagnosis out of a total of 2365 suspected cases of COVID-19 were found at Udayana University. The majority of cases of misdiagnosis involved people older than 60 years, namely 7 people (24.1%) and were dominated by men, namely 17 people (58.6%). The most common symptoms found are fever, cough, shortness of breath, headache, and malaise, According to laboratory results, dominant patients have thrombocytopenia, followed by high alanine transaminase (ALT), high aspartate transaminase (AST), and leukopenia. The appearance of thrombocytopenia in cases of COVID-19 with dengue fever is the result of suppressed platelet synthesis due to virus induction which causes bone marrow suppression and platelet clearance. Leukopenia and leukocytosis may coexist with lymphopenia as an indicator of disease severity. The similarity of symptoms and laboratory results between COVID-19 and dengue fever allows for misdiagnosis that will affect the patient's management. Therefore, the aim of this study is to determine the misdiagnosis rate of COVID-19 with dengue fever at Udayana University Hospital in 2020–2021, so that it can reduce misdiagnosis of the disease.